Factors affecting Muslim non-customers to use Islamic bank: Religiosity, knowledge, and perceived quality - Kunti Saptasari; Hendy Mustiko Aji (Jurnal Ekonomi & Keuangan Islam, 2020)
Purpose – The purpose of this paper is to determine the factors influencing the Indonesian Muslim consumer’s intention to use Islamic banks.Methodology – This paper adopts a quantitative approach. The data is collected from online and offline questionnaires. By using a non-probability purposive sampling method, this study limited the respondents to the Muslims who have no Islamic bank account. In total, there are a total of 575 sample respondents.Findings – The results of this study portray that religiosity, knowledge, and perceived quality have a positive and significant effect on customers’ intention to use Islamic bank in Indonesia.Research limitations – After finishing all research processes, the author finds that the indicators to measure Islamic religiosity is not entirely reflected Islamic religiosity from the Indonesian Muslim context. As a consequence, several items must be eliminated from the analysis due to validity issues. The author recommends future researchers to retest the religiosity indicators to find more suitable items in the context of Indonesia Muslim culture.Practical applications – This study provides an insight into the Indonesian Islamic finance industry as a basic formulation in designing, developing, and appropriate strategies to promote Islamic banking.Social applications – This study not only helps Islamic financial sector in designing, developing, and promoting Islamic banking in Indonesia but also offers new insights concerning Indonesian Muslim religiosity, knowledge on Islamic banks, and their perception of quality toward Islamic banks.Originality – This study uses an extended Theory of Planned Behavior (TPB) to explain the intention to use Islamic banks. In the model, religiosity, knowledge, and perceived quality is simultaneously tested to complement the TPB.